Regulation of lac Operon Expression: Reappraisal of the Theory of Catabolite Repression - Wanner, Barry L. (1978)
The physiological state of Escherichia coli with respect to (permanent) catabolite repression was assessed by measuring the steady-state level of β-galactosidase in induced or in constitutive cells under a variety of growth conditions. Four results were obtained. (i) Catabolite repression had a major effect on fully induced or constitutive expression of the lac gene, and the magnitude of this effect was found to be dependent on the promoter structure; cells with a wild-type lac promoter showed an 18-fold variation in lac expression, and cells with the lacP37 (formerly lac-L37) promoter exhibited several hundred-fold variation. (ii) Exogenous adenosine cyclic 3′,5′-monophosphoric acid (cAMP) could not abolish catabolite repression, even though several controls demonstrated that cAMP was entering the cells in significant amounts. (Rapid intracellular degradation of cAMP could not be ruled out.) (iii) Neither the growth rate nor the presence of biosynthetic products altered the degree of catabolite repression; all variation could be related to the catabolites present in the growth medium. (iv) Slowing by imposing an amino acid restriction decreased the differential rate of β-galactosidase synthesis from the wild-type lac promoter when bacteria were cultured in either the absence or presence of cAMP; this decreased lac expression also occurred when the bacteria harbored the catabolite-insensitive lacP5 (formerly lacUV5) promoter mutation. These findings support the idea that (permanent) catabolite repression is set by the catabolites in the growth medium and may not be related to an imbalance between catabolism and anabolism.